The odyssey to next-generation computers: cognitive computers (κC) inspired by the brain and powered by intelligent mathematics - Wang, Yingxu; Widrow, Bernard; Hoare, C. A. R.; Pedrycz, Witold; Berwick, Robert C.; Plataniotis, Konstantinos N.; Rudas, Imre J.; Lu, Jianhua; Kacprzyk, Janusz (Frontiers in Computer Science, 2023)
Cognitive Computers (kC) are intelligent processors advanced from data and information processing to autonomous intelligent generation. This work presents a retrospective and perspective review of the odyssey toward kC empowered by transdisciplinary basic research and engineering advances. A wide range of fundamental theories and innovative technologies for kC is explored, and a set of underpinning Intelligent Mathematics (IM) is created. The architectures of kC for cognitive computing and Autonomous Intelligence Generation (AIG) are designed as a brain-inspired cognitive engine. Applications of kC in Autonomous AI (AAI) are demonstrated by pilot projects. This work reveals that AIG will no longer be a human privilege via the odyssey to kC.